Current status of phenotypic and genotypic characterization of ALS resistance on common beans - Diaz, Lucy; Espitia, Ernesto; Cruz, Sergio; Lobaton, Juan; Mosquera, Gloria; Duarte, Diana (2025)
Advances are presented on the identification of resistance sources associated with the phg-2 locus in bean accessions and breeding lines, using integrated phenotyping and genotyping analyses against Pseudocercospora griseola, the causal agent of angular leaf spot